2012
DOI: 10.1017/s0025315412001270
|View full text |Cite
|
Sign up to set email alerts
|

New records of two trypetesid burrowing barnacles (Crustacea: Cirripedia: Acrothoracica: Trypetesidae) and their predation on host hermit crab eggs

Abstract: Acrothoracican barnacles of the genusTrypetesaare obligate symbionts of hermit crabs that burrow into the gastropod shells occupied by their hosts. In the present study, hermit crabs were examined for the presence of trypetesids, based on collections from the United States, Jamaica, and the Philippines made between 1997 and 2008. Shells from Jamaica and New York containedTrypetesa lateralis, a trypetesid previously documented from central California.Trypetesa lateralisis redescribed based on light and scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Other studies have showed blue-green algae-like particles in the gut of Trypetesa lampas (see Kamens 1981), and it may be that barnacles in male hermit crabs filter feed on particles from the water, whereas barnacles in females feed on the hermit crab eggs (Williams et al 2011). Murphy and Williams (2013) verified this study and suggested that the more accurate term for these barnacles may be "transient parasites" as they can be harmful in some cases but cause no harmful impact in other cases. Larsen et al (2016) added that the barnacles do not rely on the egg predation to any substantial degree and found much of the data they collected on prevalence, load, reproductive cycles, and host relationships differed from previous studies.…”
Section: Acrothoracicamentioning
confidence: 97%
“…Other studies have showed blue-green algae-like particles in the gut of Trypetesa lampas (see Kamens 1981), and it may be that barnacles in male hermit crabs filter feed on particles from the water, whereas barnacles in females feed on the hermit crab eggs (Williams et al 2011). Murphy and Williams (2013) verified this study and suggested that the more accurate term for these barnacles may be "transient parasites" as they can be harmful in some cases but cause no harmful impact in other cases. Larsen et al (2016) added that the barnacles do not rely on the egg predation to any substantial degree and found much of the data they collected on prevalence, load, reproductive cycles, and host relationships differed from previous studies.…”
Section: Acrothoracicamentioning
confidence: 97%
“…However, this was predation, not parasitism. Murphy and Williams (2013) suggested burrowing barnacles in hermit crab shells were 'transient parasites' because they somehow consumed hermit crab eggs and preferred female hermit crab shells. In our opinion, burrowing barnacles are not parasites, as least when considering the current available information.…”
Section: Life Cyclementioning
confidence: 99%